The effectiveness and safety of acupuncture for chemotherapy-induced peripheral neuropathy: A systematic review and meta-analysis - Xu, Zhonghang; Wang, Xingbo; Wu, Yuanyu; Wang, Chengbing; Fang, Xuedong (Frontiers in Neurology, 2022)
Objectives This systematic review and meta-analysis aimed to evaluate the effectiveness and safety of acupuncture on chemotherapy-induced peripheral neuropathy (CIPN). Methods We searched for relevant randomized controlled trials (RCTs) in PubMed, Cochrane Library, and Embase databases from their inception to 1 April 2022. The Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx), Brief Pain Inventory-Short Form (BPI-SF), the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core30 (EORTC QLQ-C30), Numerical Rating Scale (NRS), and adverse events were the outcome measures. All studies had at least one of these outcome measures. Mean differences (MDs) with 95% confidence intervals (CIs) were assessed in the meta-analysis using the RevMan 5.3 software. Results Five studies were included in the analysis. The results showed that acupuncture and placebo acupuncture were not significantly different in reducing chemotherapy-induced neurotoxicity and functional disability (random-effects estimates; MD: 4.30; 95% CI: −0.85 9.45; P = 0.10; I2 = 74%). Acupuncture was better than placebo acupuncture in reducing pain severity and pain interference with patients' daily function (fixed-effect estimates; MD: −1.14; 95% CI: 1.87 to −0.42; P = 0.002; I2 = 13%). Acupuncture was not significantly different from placebo acupuncture in relieving CIPN symptoms (MD: −0.81; 95% CI: −2.02 to 0.40, P = 0.19). Acupuncture improved quality of life better than placebo acupuncture (MD: 10.10; 95% CI: 12.34 to 17.86, P = 0.01). No severe adverse events were recorded in all five studies. Conclusion This meta-analysis suggests that acupuncture may be more effective and safer in reducing pain severity and pain interference with patients' daily function than placebo acupuncture. Additionally, acupuncture may improve the quality of life of patients with CIPN. However, large sample size studies are needed to confirm this conclusion. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=324930, identifier: CRD42022324930.